Strain and Dimension Effects on the Threshold Voltage of Nanoscale Fully Depleted Strained-SOI TFETs - Yu-Chen Li; He-Ming Zhang; Shu-lin Liu; Hui-Yong Hu (Advances in Condensed Matter Physics)
A novel nanoscale fully depleted strained-SOI TFET (FD-SSOI TFET) is proposed and exhaustively simulated through Atlas Device Simulator. It is found that FD-SSOI TFET has the potential of improved on-current and steep subthreshold swing. Furthermore, the effect of strain and dimension on the threshold voltage of FD-SSOI TFET is thoroughly studied by developing a model based on its physical definition. The validity of the model is tested for FD-SSOI TFET by comparison to 2D device simulations. It is shown that the proposed model can predict the trends of threshold voltage very well. This proposed model provides valuable reference to the FD-SSOI TFETs design, simulation, and fabrication.